2008
DOI: 10.1007/s10494-008-9148-0
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Source-Term Estimation as a Method for Chemical Closure in Premixed Turbulent Reacting Flow

Abstract: A Conditional Source-term Estimation (CSE) model is used to close the mean reaction rates for a turbulent premixed flame. A product-based reaction progress variable is introduced as the conditioning variable for the CSE method. Different presumed probability density function (PDF) models are studied and a modified version of a laminar flame-based PDF model is proposed. Improved predictions of the variable distribution are obtained. The conditional means of reactive scalars are evaluated with CSE and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…While the correctness of the modified laminar-flame-based PDF of Jin et al [33] as compared to the b-distribution for premixed flames has been demonstrated by Salehi et al [34,35], for LES of premixed flames in the flamelet regime with relatively low turbulence intensities, the differences in the predicted solutions obtained using the modified laminar-flame-based and b PDFs have been found to be rather small [34e36]. For this reason, it is felt that the b-PDF is sufficiently accurate for the hydrogen-enriched flames of interest and is used here.…”
Section: Pcm-fpi Combustion Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…While the correctness of the modified laminar-flame-based PDF of Jin et al [33] as compared to the b-distribution for premixed flames has been demonstrated by Salehi et al [34,35], for LES of premixed flames in the flamelet regime with relatively low turbulence intensities, the differences in the predicted solutions obtained using the modified laminar-flame-based and b PDFs have been found to be rather small [34e36]. For this reason, it is felt that the b-PDF is sufficiently accurate for the hydrogen-enriched flames of interest and is used here.…”
Section: Pcm-fpi Combustion Modelmentioning
confidence: 96%
“…Note that other choices for the presumed PDF of c are possible, including the original and modified laminar-flamebased PDFs of Bray et al [32] and Jin et al [33], respectively. While the correctness of the modified laminar-flame-based PDF of Jin et al [33] as compared to the b-distribution for premixed flames has been demonstrated by Salehi et al [34,35], for LES of premixed flames in the flamelet regime with relatively low turbulence intensities, the differences in the predicted solutions obtained using the modified laminar-flame-based and b PDFs have been found to be rather small [34e36].…”
Section: Pcm-fpi Combustion Modelmentioning
confidence: 99%
“…Conditional Moment Closure (CMC) approaches [34][35][36][37][38][39][40] attempt to describe chemistry by solving for values of chemical species that have been conditioned on a particularly relevant scalar. A mixture fraction or progress variable is typically used for this purpose.…”
Section: Conditional Moment Closure Modelsmentioning
confidence: 99%
“…An approach that is closely related to CMC is Conditional Source term Estimation (CSE) [38,39]. In this approach, independent variables are not added to the problem's dimensionality or to the computational mesh.…”
Section: Conditional Moment Closure Modelsmentioning
confidence: 99%
See 1 more Smart Citation